Scratch resistance and tribological properties of SiOx incorporated diamond-like carbon films deposited by r.f. plasma assisted chemical vapor deposition. (April 2015) - Kumar, N.; Barve, S.A.; Chopade, S.S.; Kar, Rajib; Chand, N.; Dash, S.; Tyagi, A.K.; Patil, D.S.
Abstract: SiO x containing diamond-like carbon (DLC) films are deposited on the stainless steel 316 substrates by radio frequency (r.f.) plasma assisted chemical vapor deposition (PACVD) process using plasma of Argon, methane gases and Hexamethyl Disiloxane vapors. The sp 3 /sp 2 ratio of carbon bonding in the films is found to increase with increase in bias. Films deposited at low bias voltage (-25 V) show onset of film spallation and critical failure during scratch test at low progressive load and it has high friction coefficient. In contrast, film deposited at −100 V bias shows low coefficient of friction <0.05. Such a low friction coefficient is related to optimum fraction of sp 2 carbon bonding and a-C contents. Highlights: SiO x containing DLC films are deposited r.f. PACVD process varying r.f. self bias. Investigation of scratch resistance and tribological properties at various loads. Scratch induced failure mechanism. Low friction coefficient in sp 2 /a-C dominated film.